The emperor redressed : critiquing critical theory - Eddins, Dwight, 1939- (University of Alabama Press, 1995)
The essays in this volume represent a collective questioning of the poststructuralist ascendancy, and of the assumptions involved therein, by a group of prominent scholars and critics: M.H. Abrams, Nina Baym, Frederick Crews, Ihab Hassan, David Lehman, Richard Levin, Paisley Livingston, Saul Morson, and John Searle.